WEB-BASED AUDIO MATERIALS FOR EFL LISTENING CLASS - Putu Suarcaya (TEFLIN, 2011)
Abstract: The present study aimed at finding out the response of learnÂers in an EFL Listening class to the use of web-based listening tasks and their academic achievement in the class. The subjects of the study were 22 university students. The method employed was mixed method. Data were collected using questionnaire and achievement tests. The results showed that 90.9% of the learners enjoyed and were interested in the on-line activity. The t-test analyses also showed that there was significant difference between the Means of scores of learners in the midterm test and final test on Listening 1 and Listening 2.